Prophylactic Warming Mung Bean Bag to Prevent Hypothermia in Parturients Undergoing Cesarean Delivery during Spinal Anesthesia - kantanabat, Chonrat (Thai Journal of Anesthesiology, 2021)
Background: Hypothermia is a common incidence in the patient who underwent surgery under spinal anesthesia. Perioperative hypothermia causes many serious complications. Prophylaxis hypothermia during surgery can decrease this incidence. Objectives: To compare the incidence of a mung bean bag with a placebo to prevent hypothermia in parturients undergoing cesarean delivery during spinal anesthesia. Methods:A prospective randomized control trial, fifty-four patients undergoing cesarean delivery during spinal anesthesia. Patients were randomly allocated to received normal saline (n=27) or normal saline cover with a mung bean bag (n=27). Tympanic temperature, shivering score and side effects were also recorded. Results: The incidence of postoperative hypothermia and shivering were significantly less in group M. No major side effects were found. Conclusion: Prophylactic warming mung bean bag could prevent hypothermia in parturients undergoing cesarean delivery during spinal anesthesia without causing any major untoward side effects.